EFFECTS OF GOVERNMENT INPUT SUBSIDY PROGRAM ON MAIZE PRODUCTION IN UASIN-GISHU COUNTY - Isaac, Magut; Wachira, Dr. Anita; Mwenda, Dr. Lilian (Journal of Public Policy and Administration, 2019)
Purpose: Food shortage witness in the Kenya has continued regardless of the government effort to reverse the situation through various interventions put in place, compelling the government to resort to importation as a means of plugging off the deficit. It is against this that the study focus on the effects of government input subsidy program as one of the government interventions on maize production and The study was based on social protection theory by United Nation Institute of Research and Social Development (UNIRSD). Methodology: The study adopted descriptive research design and utilized a sample frame of 396 respondents who were purposively sampled from a population of 40000 active maize farmers within Uasin Gishu County comprising of both small and large scale farmers registered by county agricultural office. The sample size was further shared among the three Sub counties namely; Eldoret West, Wareng and Eldoret East based on their proportionate population of farmers. The data was collected by use of questionnaires. The researcher collected quantitative data by use of questionnaires and analyzed by use of descriptive statistics and the relationships between the independent variables and dependent variable was established by use of regression analysis both multi and linear regression statistic techniques. Statistical package for social science (SPSS) Version 24 software was used to analyze quantitative data and outcome presented inform of graphs, pie charts and tables. Findings: The study established that there was significant positive relationship between government input subsidy program (R2=31.7%, F= 166.050% and P-Value= 0.000). The study concludes that government input subsidy program has a significant positive relationship effect on maize production as depicted by a significant p-value of 0.000. Unique contribution to theory, practice and policy: The study recommends that the government should ensure farmers get farm inputs in time and at reasonable price in order to enable them produces more maize.